Teknik Penyembunyian Data Non-Destruktif pada Citra Digital Menggunakan Metode End-of-File (EOF) dan Enkripsi AES-256 - Muhammad Ulya Farhan; Fathul Barri Akbar; Ammar Fatin; Ariifah Yaasir Harahap (JIKUM: Jurnal Ilmu Komputer, 2026)
Conventional cryptography and LSB steganography often suffer from detectability and visual distortion. This study proposes a non-destructive solution integrating End-of-File (EOF) steganography with AES-256 encryption to ensure data security without compromising carrier media quality. The method functions by appending encrypted data after the image file terminator, leaving the original pixel structure intact. Security is reinforced using AES-256 (CBC mode) and PBKDF2-HMAC-SHA256 with 100,000 iterations. Experimental results using the "PrivaSel" interface demonstrate perfect visual integrity, evidenced by identical histograms between original and stego images. Validation via Hex Editor confirms data insertion through a unique "AES-EOF" marker. Consequently, this system achieves an optimal balance between confidentiality and invisibility, preserving 100% of carrier media integrity for secure digital exchange.